How to avoid knee tunnel convergence when performing a combined anterior cruciate ligament reconstruction and lateral extraarticular tenodesis utilizing the antero medial window - Espiritu, Wesson Pious A.; Sanchez, Melissa Mae R. (International Journal of Research in Orthopaedics, 2023)
The anterolateral structures of the knee have been demonstrated to have a significant impact on reducing rotational instability and the forces applied to the anterior cruciate ligament reconstruction (ACL) graft after surgical reconstruction. Combined ACL reconstruction and lateral extraarticular tenodesis are being performed at an increasing number due to its promising outcome in properly indicated patients. However, tunnel convergence in combined ACLR and lateral extraarticular tenodesis can lead to graft damage and possible failure defeating the purpose of this very effective technique. This technical note describes how to avoid knee tunnel convergence when performing a combined ACL reconstruction with lateral extraarticular tenodesis utilizing the “Antero medial window”.